Dampak Pandemi Covid-19 Bagi Para Tenaga Kerja Teknisi - Dhiyaul Auliyah; Martinus Legowo (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2022)
The Covid-19 pandemic has had a significant impact on various aspects of life, including the economy. Economic actors such as companies also experienced a decline in the economy. The losses experienced by the company also affect the workforce working in the company, including in this case the technicians. The purpose of this study was to identify the experiences of technician workers affected by the Covid-19 pandemic in Surabaya. The approach used in this study is a qualitative descriptive approach with interviews and literature studies. The data were analyzed using phenomenological theory by Hans Georg Gadamer. The results showed that the company suffered significant losses due to the Covid-19 pandemic, so it had to decide to reduce the technician workforce. The impact received by the technician workforce includes being transferred to another branch of the company, as well as being laid off. Some of the disturbances experienced by workers such as having to adapt to a new environment, learning to understand tasks from scratch and economic difficulties. In Gadamer's view of phenomenology, the expression of technicians is a form of explanation and expression of the experience of participation and openness. The workers do not necessarily despair over the existing disturbances, because of the efforts made ranging from adaptation, business, and learning, to opening their businesses over time the workers begin to adapt to current conditions. The workers hope that the Covid-19 pandemic will end soon and the economy can return to normal as before.